Do corporate governance mandates impact long-term firm value and governance culture? - Aggarwal, Reena; Schloetzer, Jason D.; Williamson, Rohan (Journal of Corporate Finance, 2019)
Motivated by recent changes to corporate governance standards around the world, we use a regulatory shock that substantially altered the governance structure for some firms to shed light on the long-term impact of mandates that are of global interest. Firms affected by this shock had lower values and non-mandated governance practices that were less shareholder friendly before the mandates were in effect when compared to unaffected matched peers. In the post-mandate period, we document a 48% tightening of the relative value gap, and show that this gap relates to the continued use of less shareholder friendly non-mandated governance practices. Our results suggest that governance mandates can tighten, but not eliminate, the value gap between poorly and well governed firms, and that firms affected by the shock continue to have less shareholder friendly governance cultures long after regulatory intervention.